A repurposed space: City God Temple as National Products Exhibition Hall in Guangzhou, 1928 to 1937 - Liu Xiaoqing (Journal of Asian Architecture and Building Engineering)
Guangzhou’s City God Temple, originally built in 1370, remained one of Guangzhou’s most-enduring examples of architectural heritage well into the twentieth century, especially between 1928 and 1937. Long considered a landmark – both spatially and aesthetically – by local and international visitors, the temple’s social roles within the city and its adaptation to changes initiated by Guangzhou government, particularly from a religious space into a National Products Market from 1928 to 1937, have not been well studied by scholars. This research examines the temple’s history during that specific period – a decade of political and social change inspired by anti-religious and anti-superstitious state campaigns that had a consequential effect on the temple’s broader significance as a civic space. A closer look at proposed changes initiated by the Committee of Ritual Reformation and the National Products Movement reveals the temple’s contributions to state campaigns to promote Nationalist thoughts and the city’s physical expansion. The research methods included site investigation and examination of historical archives, including old maps, newspapers, journals, government gazettes, and archival records. By studying the reformation process of this particular temple, this article contributes to expanding our understanding of blurring social orders of republican Guangzhou that were taking place amid growing nationalism.